Indications and outcomes of liver retransplantation in three medical centers - WAGNER AUGUSTO SCHIEL; JULIO CEZAR UILI COELHO ECBC-PR; ANDRE LUIS CONDE WATANABE TCBC-DF; MARCO AURÉLIO RAEDER DA COSTA; ALCINDO PISSAIA JÚNIOR (Revista do Colégio Brasileiro de Cirurgiões, 2024)
ABSTRACT Introduction: retransplantation is the only viable treatment for patients with irreversible graft loss. The objective of this study was to analyze the indications and outcomes of liver retransplantation in three medical centers. Methods: a total of 66 patients who underwent liver retransplantation from September 1991 to December 2021 were included in the study. A retrospective analysis was performed evaluating patients demographic, clinical, primary diagnosis, indications for and time interval to retransplantation, complications and patient survival. Results: from a total of 1293 primary liver transplants performed, 70 required one or more liver retransplant. The main indication for primary transplant was hepatitis C cirrhosis (21,2%). Hepatic artery thrombosis was the main cause of retransplantation (60,6%), with almost half (46,9%) of retransplants having occurred within 30 days from initial procedure. The average survival time after a repeat liver transplant, was 89,1 months, with confidence interval from 54 to 124,2. The 1-,5- and 10- year survival rate following liver retransplant were 48,4%, 38% and 30,1%, respectively. Male gender, primary non function as the cause for retransplant, prolonged operative time and higher MELD were associated with higher mortality. Conclusions: operative mortality and morbidity rates of liver retransplantation are higher than those of the first transplantation. Male gender, primary non function, prolonged operative time and higher MELD were associated with less favorable outcomes.